2004
DOI: 10.1159/000080664
|View full text |Cite
|
Sign up to set email alerts
|

Social Hierarchy Affects Gene Expression for Catecholamine Biosynthetic Enzymes in Rat Adrenal Glands

Abstract: Social stressors, like other stressors, are powerful activators of the sympathoadrenomedullary system. Differential housing (single vs. group) and social defeat of rats is known to alter the activity of catecholamine-synthesizing enzymes in the medulla. The present studies examined the effect of 70 days of triad (3 rats per large cage) and individual housing of male rats on adrenal mRNA levels of tyrosine hydroxylase (TH), dopamine-β-hydroxylase (DBH) and phenylethanolamine-N-methyltransferase (PNMT) and on TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…In confirmation of our previous neurobiological findings (Pohorecky et al 1999(Pohorecky et al , 2004a, the present data indicate that singly housed rats differ from triad-housed rats. For example, while singly and triad-housed rats did not behave substantially differently in the open field following a saline injection, their response to EtOH differed from that seen in triad rats (e.g., for locomotor behavior but not for other parameters such as head-poke).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In confirmation of our previous neurobiological findings (Pohorecky et al 1999(Pohorecky et al , 2004a, the present data indicate that singly housed rats differ from triad-housed rats. For example, while singly and triad-housed rats did not behave substantially differently in the open field following a saline injection, their response to EtOH differed from that seen in triad rats (e.g., for locomotor behavior but not for other parameters such as head-poke).…”
Section: Discussionsupporting
confidence: 93%
“…On day 1 of the study, subjects were placed into a novel triad cage, and the social interactions were recorded during the first 30 min of group housing. Agonistic behaviors were scored using an expanded version of the method originally described by Peterson and Pohorecky (1989) but applying its expanded version (Pohorecky et al 1999(Pohorecky et al , 2004a. Briefly, offensive and defensive aggressive behaviors (including roll-tumble fights, on top, lateral threat, freezing, defensive upright, and fleeing) and piloerection were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is recognised that psychological stressors result in catecholaminegic responses [15,16], how this process is regulated by TH phosphorylation has not been examined. We therefore examined TH phosphorylation in vivo following exposure of rats to either a novel environment or after social defeat, a well characterised psychological stressor [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since housing density is an independent determinant of level of stress [26], we separately analyzed data by density of home cage housing. Neonatally handled rats that were housed in groups of 3 did not develop hyperalgesia when exposed to the water-avoidance stress protocol (1-way repeated measures ANOVA, F 3,54 =114, p =0.338), while those housed in groups of 2 developed hyperalgesia (1-way repeated measures ANOVA, F 3,57 =12.46, p =0.0002, Figure 3), with a significant difference between baseline nociceptive threshold and threshold measured at days 1, 2 and 3 (Dunnett’s multiple comparison test, p <0.05, Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that rats housed 2 per cage spent only about one fifth the time in the open arm of the elevated plus maze compared to rats housed 3 per cage (and a similar amount of time to solitary housed rats), indicating that there is a significantly greater chronic anxiety level in rats housed 2 per cage [46]. Of note, anxiety is closely correlated with stress hormone levels [47], and housing density is known to affect both the rate of catecholamine synthesis as well as magnitude of release from the adrenal medulla [26]. Other measures of stress level, resting mean arterial pressure and heart rate, were both significantly less for rats housed 4 per cage than for those housed 1 or 2 per cage, and the cardiovascular responses to a mild stressor (regular cage change) was also significantly less in rats housed 4 per cage [48].…”
Section: Discussionmentioning
confidence: 99%